(untitled) (Al-Ilmu, 2025)
Background: Islamic education management requires a strong humanitarian foundation rooted in prophetic traditions (hadith) that emphasize human dignity, moral values, and ethical conduct in administrative duties. The integration of humanitarian values ​​based on religious, moral, and ethical principles in educational management remains a critical yet understudied aspect of contemporary Islamic education. Objective: This study aims to analyze hadith teachings about upholding humanitarian values ​​in performing administrative duties within Islamic education management, focusing on religious, moral, and ethical dimensions. Method: This research employs qualitative methodology with thematic hadith analysis, examining authentic prophetic traditions that emphasize humanitarian values, supported by classical Islamic scholarship and contemporary educational management theories. Results: The study identifies four core humanitarian principles from hadith: respect for human dignity (karamah insaniyyah), compassion (rahma), justice and fairness (adl wa qist), and moral accountability (mas’uliyyah akhlaqiyyah) in educational administration. Conclusion: Hadith provides comprehensive guidance for humanitarian-centered Islamic education management that prioritizes human dignity, moral integrity, and ethical conduct as fundamental principles in administrative practices.